Handbook of Outpatient Medicine (Springer International Publishing, 2018)
This handbook provides a quick, portable, algorithm-based guide to diagnosis and management of common problems seen in adult patients. Written by experienced primary care practitioners, the book emphasizes efficient decision making necessary in the fast-paced realm of the medical office. It covers general considerations such as the physical examination, care of special populations, and pain management and palliative care. It also focuses on common symptoms and disorders by system, including endocrine, respiratory, cardiac, orthopedic, neurologic, genitourinary, and gynecologic. For each disorder, symptoms, red flags, algorithms for differential diagnosis, related symptoms and findings, laboratory workup, treatment guidelines, and clinical pearls are discussed. Handbook of Outpatient Medicine is a valuable resource for primary care physicians, residents, and medical students. .